Penggunaan Media Sosial TikTok oleh Tanoto Foundation untuk Menjangkau Generasi Z - Muris, Dendy; Toroxandy, Mirakel Alantaurizqa; Rahmawati, Salsabila Dian (Ikatan Sarjana Komunikasi Indonesia, 2023)
As a philanthropic foundation, the Tanoto Foundation has unique programs with individual educational development. Teladan is a program that guides the younger generation to create a quality generation and prepare the next generation of leaders. Generation Z is the current generation that Tanoto is focused on. There are challenges in preparing Generation Z as future leaders. Based on the data, generation Z has a low interest in learning. Apart from that, Generation Z prefers social media when looking for information. For this reason, Tanoto is trying to use TikTok social media to facilitate Generation Z to be more interested in education and increase digital literacy for the future. This research seeks to find out how the TANOTO Foundation uses TikTok as an informal educational forum for Generation Z through edutainment content. The research was carried out using a qualitative approach and interview and observation methods as data collection techniques. The research results show that through designing, targeting and producing content with an attractive edutainment concept, Tanoto can reach and attract Generation Z. Edutainment content and the role of the Tanoto Foundation as an agent of change through TikTok can continue to be improved through TikTok social media optimization efforts that focus on engaging and more interactive audiences.Keywords: Philanthropy, Tanoto, Social Media, TikTok